Cryptocurrency from shariah perspective - Nadiyah Syahira binti Nordin (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
Cryptocurrency is seen to create a new phenomenon to the landscape of financial services industry. It has gained attention in attracting all relevant players in the industry to delve deeper into the issue. Preceding bitcoin as the inaugural prevalent product, cryptocurrency has been utilized as the medium of payment in various sectors. Owing to that factor, it is conceivable why it is taken as a new phenomenon. Islamic finance, being an integral part of financial industry, also concerned about this new emergence. The usage of cryptocurrency penetrated Islamic finance through the introduction of Mudharabah-based offering for small enterprises by Blossom Finance. Owing to this observance, this calls for an academic approach of cryptocurrency analysis from Shariah perspective. This is due to the reason that practices in Islamic finance without proper Shariah deliberation may run the risk of non-compliance. This research sought to identify the concept of cryptocurrency from its features and process. The technical features comprising of validating mechanism, mathematical algorithm and coins supply are analysed in the context of the fulfilment of currency prerequisites from Shariah perspective. The prerequisites, which are derived from the views of classical and contemporary scholars, are capturing the function of money that are notably being the medium of exchange, store of value, being commonly acceptable within a community and having a legal tender status. Through the analysis conducted of examining the technical features of cryptocurrency against the currency prerequisites and requirements, it is apparent that the technical features of cryptocurrency satisfy the prerequisites of currency from Shariah perspective except for the legal tender status. However, that does not deny the other fulfilment and consideration that cryptocurrency could serve the function as medium of payment although greater emphasis is on the legal tender title of a currency.